Emotions in physical education from the constructivist perspective: analysis of the curriculums of Spain and Chile - Mujica, Felipe Nicolás; Orellana, Nelly del Carmen (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The main theories of constructivist learning recognize the emotional dimension as an essential component of the educational act, since it is one of the mediating elements in the interpretation and meaning of reality. This perspective has impacted all the disciplines of the curriculum and specifically that of Physical Education, which is a very special subject, since it requires learners to be involved in all its dimensions, where in addition the social exposure is usually a very common situation. Given this scenario, elements of the Spanish and Chilean curriculums have been analyzed, with the aim of describing the incorporation and systematization of emotions, understanding that this measure is fundamental to guarantee a comprehensive education. From this analysis, it can be said that the Spanish educational legislation has systematized different competences that include that dimension, while the Chilean legislation has incorporated attitudinal objectives that include the affective dimension, but no rigorous programming is appreciated. Therefore, it is concluded that there is a need to open a debate on integral education in Chile.